2019
DOI: 10.31744/einstein_journal/2020rw4890
|View full text |Cite
|
Sign up to set email alerts
|

The direct and indirect effects of the pneumococcal conjugated vaccine on carriage rates in children aged younger than 5 years in Latin America and the Caribbean: a systematic review

Abstract: The direct and indirect effects of the pneumococcal conjugated vaccine on carriage rates in children aged younger than 5 years in Latin America and the Caribbean: a systematic review Efeitos diretos e indiretos da vacina pneumocócica conjugada no estado de portador em crianças menores de 5 anos, na América Latina e no Caribe: uma revisão sistemática

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The overall carriage in our study was very high and remained high 4 years after introduction which is comparable to what has been reported previously in several other studies from low and middle-income countries. A study in Kenya reported an overall carriage rate of 76% in under 5 children, five years after introduction of PCV10 [25] , overall carriage was 85% in The Gambian children aged 6–12 months 5 years after introduction of PCV13 [23] , [33] . In Mozambique two years after introduction of PCV10, the overall carriage was 84.8% in children under 5 years of age [26] .…”
Section: Discussionmentioning
confidence: 99%
“…The overall carriage in our study was very high and remained high 4 years after introduction which is comparable to what has been reported previously in several other studies from low and middle-income countries. A study in Kenya reported an overall carriage rate of 76% in under 5 children, five years after introduction of PCV10 [25] , overall carriage was 85% in The Gambian children aged 6–12 months 5 years after introduction of PCV13 [23] , [33] . In Mozambique two years after introduction of PCV10, the overall carriage was 84.8% in children under 5 years of age [26] .…”
Section: Discussionmentioning
confidence: 99%